2019
DOI: 10.1002/ange.201908649
|View full text |Cite
|
Sign up to set email alerts
|

From Bad Electrochemical Practices to an Environmental and Waste Reducing Approach for the Generation of Active Hydrogen Evolving Electrodes

Abstract: The electrodeposition of noble metals using corresponding dissolved metal salts represents an interesting process for the improvement of the electrocatalytic hydrogen evolution reaction (HER) properties of less active substrate materials. The fact that only a small fraction of the dissolved noble metals reaches the substrate represents a serious obstacle to this common procedure. We therefore chose a different path. It was found that the HER activity of Ni42 alloy drastically increased (η=140 mV at j=10 mA cm−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Acoustic cavitation phenomena are usually associated with the formation, growth, and collapse of cavitation bubbles induced by the propagation of an ultrasonic wave in a liquid and, consequently, to the generation of very high pressures, shear stresses, and temperatures locally. The collapsing bubble event is a microscopic implosion that generates high local turbulence and thermal energy, e.g., generating high temperatures up to 5000 °C and high pressures up to 2000 atm. , Recently, it was found that ultrasonication greatly improves the electrocatalytic properties of surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…Acoustic cavitation phenomena are usually associated with the formation, growth, and collapse of cavitation bubbles induced by the propagation of an ultrasonic wave in a liquid and, consequently, to the generation of very high pressures, shear stresses, and temperatures locally. The collapsing bubble event is a microscopic implosion that generates high local turbulence and thermal energy, e.g., generating high temperatures up to 5000 °C and high pressures up to 2000 atm. , Recently, it was found that ultrasonication greatly improves the electrocatalytic properties of surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…However, its scarcity on earth and high price make it unsuitable for widespread adoption. A few recent works have demonstrated high catalytic activity using less Pt on electrodes [16]. Nevertheless, it is still necessary to explore earth-abundant and inexpensive electrocatalysts for hydrogen production [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%